CompTIA Network+ certification study guide - Clarke, Glen E (New Delhi Tata McGraw-Hill, 2012)
"Exam-focused test prep and review--fully updated for the 2011 revision to the CompTIA Network+ examCompTIA Network+ Certification Study Guide, Fifth Edition offers complete coverage of the objectives for the new CompTIA Network+ exam, and provides an integrated study system based on proven pedagogy. Certification objectives are called out in every chapter. Series features reinforce and teach practical skills, including: step-by-step exercises, exam watch and on-the-job elements, and chapter self tests. The self-test sections include knowledge and scenario-based questions and one case study-based lab question per chapter. This complete study system includes more than 400 practice exam questions (in the book and on CD) that match the actual exam questions in content and style. The fifth edition has been thoroughly revised and updated to cover new exam areas, including Windows Server 2009, and the latest networking data and information.CompTIA Network+ Certification Study Guide, Fifth Edition Includes a bonus lab book in electronic form with 20+ additional labs that don$1 (Bt appear in the book Features authorized CompTIA Authorized Partner Program (CAPP) content and is CompTIA reviewed and approved: CAQC (CompTIA Approved Quality Curriculum) Contains a CD-ROM with two full practice exams, video training from the author, and a PDF copy of the book Covers all exam topics: Basic Network Concepts; Network Protocols and Standards; Network Components; TCP/IP Fundamentals; Subnetting and Routing; TCP/IP Utilities; Configuring Network Services; Wireless Networking; Remote Connectivity; Wide Area Network Technologies; Implementing a Network; Maintaining and Supporting a Network; Network Security; Troubleshooting the Network"-- |c Provided by publisher.s
"With hundreds of practice questions and hands-on exercises, CompTIA Network+ Certification Study Guide, Fifth Edition covers what you need to know--and shows you how to prepare--for this challenging exam"-- |c Provided by publisher.
Machine generated contents note: Chapter 1: Basic Network Concepts -- Chapter 2: Network Protocols and Standards -- Chapter 3: Networking Components -- Chapter 4: TCP/IP Fundamentals -- Chapter 5: TCP/IP Utilities -- Chapter 6: Configuring Routers and Switches -- Chapter 7: Subnetting and Routing -- Chapter 8: Configuring Network Services -- Chapter 9: Wireless Networking -- Chapter 10: Remote Access and VPN -- Connectivity -- Chapter 11: Wide Area Network Technologies -- Chapter 12: Implementing a Network -- Chapter 13: Maintaining and Supporting a Network -- Chapter 14: Network Security -- Chapter 15: Troubleshooting the Network.
Includes index
Keywords: Computer networks -- Examinations -- Study guides; Telecommunications engineers -- Certification